Emerging Technologies for Sustainable Universities and Colleges: A Meta-Synthesis - Tarraya, Hilger O.; Camposano, Charlyn E.; Rojo, Sarah G.; Dolorica, Maria Crestina C.; Polon, Jeric H.; Digo, Gerry S. (ASEAN Journal of Educational Research and Technology, 2025)
Sustainability is a key concern in modernizing higher education. This paper reviews how emerging technologies are integrated to promote sustainability in universities and colleges, analyzing various technologies, benefits, drivers, and barriers using the STARLITE framework. Key technologies include web and internet technologies, online assessment systems, green computing, advanced data analytics and AI tools, smart infrastructures, Bluetooth beacons, digital transformation, e-Learning/LMS, simulation-based education, gamification, and MOOCs. These technologies enhance student learning outcomes and campus efficiency. Successful integration requires strong leadership, relevant curriculum, and stakeholder involvement. Barriers include technological issues, misconceptions of sustainability, lack of financial resources, and stakeholder apathy. Institutional leaders play crucial roles in aligning goals towards sustainability with these technologies.